Strategi Pemberdayaan UMKM Melalui Digitalisasi Keuangan untuk Keberlanjutan Bisnis - Yuli Ermawati; Pujianto; Endah Supeni Purwaningsih (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study generally aims to explore MSME empowerment strategies through financial digitalization using a descriptive qualitative approach. The specific objectives of this study are to describe MSMEs' perceptions and experiences of financial digitalization, identify supporting and inhibiting factors in financial digitalization in MSMEs, and formulate MSME empowerment strategies through financial digitalization. Data were obtained through in-depth interviews with MSME actors, MSME facilitators or academics, and the Surabaya City Cooperatives, MSMEs, and Trade Office. The results indicate that financial digitalization can be a tool for MSME empowerment if accompanied by intensive mentoring, simplification of accounting technology, multi-stakeholder collaboration, and strengthening digital financial literacy. This study produces a digital-based MSME empowerment model that emphasizes financial behavior transformation and gradual technology adaptation.